ANALYSIS OF LEADERSHIP STYLE AT PT PREMIUM CENTRAL INDOSARANA BOGOR CITY - Lily Setyawati Kristianti; Erika Aprilyani; Irfan Rizka Akbar (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to determine the Leadership Style at PT Premium Central Indosarana, Bogor City. This study uses a descriptive qualitative approach. Data collection techniques used in this study were observation, interviews, documents and triangulation. In addition, this study used SWOT data analysis to analyze the company's strengths, weaknesses, opportunities and threats. The results of the study show that leaders at PT Premium Central Indosarana Bogor City apply a democratic leadership style, which can be seen from several aspects of leaders who always conduct deliberations, accept ideas from employees, always provide motivation and enthusiasm for employees, leaders provide the right direction to subordinates. The impact of a democratic leadership style for employees is that it will provide or encourage work passion, morale, and high employee work productivity so that they can achieve the goals that have been previously set.